HgCrCdSe as an element of new heterostructure HgCrCdSe/HgMnTe - Bekirov, B.; Ivanchenko, I.; Popenko, N.; Tkach, V. (Functional Materials, 2012)
By using the EPR method we show that the introduction of the fourth component as the cadmium (Cd) into the solid solution CrₓHg₁₋ₓSe allows for increasing the transition temperature of magnetic ordering in this compound. The resistance, magnetoresistance, and current-voltage characteristics of new heterojunctions HgCdCrSe/HgMnTe are measured as a function of temperature and external magnetic field. The appearance of nonlinear plot on the reverse branch of experimental current-voltage characteristic at a temperature below the temperature of magnetic ordering can be explained by the appearance of spin-polarized current.